(untitled) (Edad Media. Revista de Historia, 2023)
The aim of this article is to analyze the community social structure of two councils of the region of Avila at the end of the 15th century. The study of taxpayer’s registers from Bonilla de la Sierra and Olmedos´s will allow us to verify that the differentiation process does not occur in a homogeneous way, even in two councils of the same region. Furthermore, we verify the phenomenon of differentiation is not exclusive to the rural world. Finally, we identify some of the characteristics of the village´s upper strata. The privileged patrimonial situation is accompanied and reinforced by the fulfillment of political and management tasks in the community.